Sintomas respiratórios e fatores relacionados - Almeida, André Augusto Gonçalves de (2016)
Respiratory symptoms are an important cause of mothers seeking health services; We can characterize them according to the presence of one or more symptoms, such as coughing, wheezing, difficulty breathing, runny nose; the study aimed to examine the respiratory symptoms and related factors in children and 36 months. Crosssectional study a nested cohort "etiological factorsof preterm birth and perinatal factors consequences in child health: birth cohorts in two Brazilian cities" – BRISA (Brasilian Birth Cohort Studies) the sample used were the information of the second moment of the cohort, conducted with mothers and children, these 1 to 3 years, with total 3306. The results showed the mother's other children (50.03%), lives with up to 4 people at home (68.43%), have an income less than minimum salary (26.76%), do not have adequate schooling to the age (35.30%), children were breastfed exclusively until the sixth month of life (59.09%), were born of natural childbirth (51.16%), respiratory symptoms (46.52%), father/mother or brothers with a history of asthma (15.48%) parent or sibling with a history for rhinitis (30.01%). The relationship between the independente and dependent variables was estimated in univariate analysis Chi-square test with a significance level of 5%. There was statistical significance between the variable respiratory symptoms and the presence of other children (57.41%) p=0.0001, economic class C(53.39%) p=0.007, children born of natural childbirth p=0.005, asthma and family history (61.72%) p=0.0001, family history for rhinitis (57.42%) p=0.003, smokers in the home (58.29%) p=0.041 and adequate schooling mother (50.67%) p=< 0.0001. The study showed that the assessment of respiratory symptoms and related factors when are important instrument in the quest for better service the child and his family, the nurse should identify early those factors and be able to give attention and quality.